(untitled) (Editora Impacto Científico, 2025)
Considering that clinical and functional vulnerability in older adults results from the interaction between health conditions, functional limitations, and psychosocial factors, and that its aggravation in the outpatient setting is influenced by socioeconomic aspects and inadequate lifestyle practices, a multidimensional approach to care is imperative. The objective is to analyze the clinical-functional vulnerability of elderly people assisted by the Unified Health System, with an emphasis on secondary care. To this end, a cross-sectional study was conducted between January and September 2024 with 120 elderly people, using the Clinical-Functional Vulnerability Index and the Elderly Person’s Health Booklet as instruments. The results showed a high level of vulnerability among older participants, with a prevalence of hypertension, diabetes mellitus, cognitive impairment, and risk behaviors such as physical inactivity, smoking, and alcohol use. This reinforces the urgency of effective public policies that prioritize health promotion, disease prevention, and comprehensive care, which are fundamental to improving the quality of care for the elderly population in the Unified Health System. DOI: https://doi.org/10.56238/edimpacto2025.087-003